Adhesion to pharyngeal epithelium and modulation of immune response: Lactobacillus salivarius AR809, a potential probiotic strain isolated from the human oral cavity - Jia, G.C.; Che, N.; Xia, Y.J.; Lai, Phoency F.-H.; Xiong, Z.Q.; Wang, G.Q.; Zhang, H.; Ai, L.Z. (Journal of dairy science, 2019)
Microbiome modulators such as probiotics are known to modulate oral diseases. Very few probiotics are commercially available for use in the oral cavity. In this context, we selected human-origin Lactobacillus salivarius AR809 as a promising oropharyngeal probiotic and characterized its functional and immunomodulatory properties. Results demonstrated that AR809 could efficiently adhere to pharyngeal epithelial FaDu cells, antagonize Staphylococcus aureus, adapt to the oral environment, and modulate host innate immunity by inducing potentially protective effects. Particularly, AR809 diminished proinflammatory activity by enhancing the production of IL10 and inhibiting the expression of tumor necrosis factor-α, IL1B, inducible nitric oxide synthase, and RELA. Finally, we observed that AR809 grew efficiently when cultured in milk, suggesting that the preparation of a fermented milk product containing AR809 could be a practical way to administer this probiotic to humans. In conclusion, AR809 has high potential to adhere to the pharyngeal mucosa and could be applied in novel milk-based probiotic fermented food products.